El IUS variandi como potestad de la administración en los contratos administrativos - Ledesma Mena, Jhon Genrry (2020)
The present study entitled "The ius variandi as the power of administration in administrative contracts" which aimed to analyze this principle in order to know in depth the scope and consequences of the application of this principle since in the materialization of the It constitutes an exception to the general principle of civil contracts, which are governed by the principle of immutability of its clauses, since once the contract between the parties is signed, it cannot be modified later. For this reason, the research focuses on the documentary and field type, since methods that allow the analysis and synthesis of the information collected are used, as well as obtaining data in the field where the study was conducted. In relation to the methods used, the deductive, inductive, analytical and synthesis are indicated, which facilitated the understanding of the information from a general perspective to make the conclusions inherent to the research variables……